Uji Kinerja Mesin Petik Pucuk Teh (Tea Harvester) Tipe TS120L Pada Lahan Berbukit Dengan Kemiringan 40-60 - An’illa Agrissa Nurringge; Iswahyono Iswahyono; Siti Djamila; Amal Bahariawan (JOFE : Journal of Food Engineering, 2022)
The quantity and quality of tea products were determined by the activity of harvesting tea leaves. The performance of the picking process was influenced by the characteristics of the tea garden land. PT. Candi Loka has hilly tea gardens with slope variations up to 60o. The purpose of this research is to observe the performance of the tea picking machine TS120L on garden land with a slope of 40-60o. Parameters observed in this activity include data on total picking time, plucking speed, plucking machine width, picking area, weight of plucked tea and fuel usage. The obtained data were analyzed to obtain the value of field capacity, efficiency of plucking performance, fuel consumption and analyzed descriptively. The results showed that the average value of theoretical field capacity ha/hour, average actual field capacity 0,14 ha/hour, average efficiency 73,68 %, average actual material capacity 1347 kg/ha and average fuel consumption 1,3 liter/hour. In general, the hilly land with a slope of 40- 60o decrease the performance of the tea picking machine TS120L